Pemahaman Keaksaraan Awal Anak Kelompok B Di TK Aisyiyah Bustanul Athfal 23 Dengok - Putri, Rosalina Trisna; Ifadah, Ayunda Sayyidatul; Fatmawati, Fitri Ayu (Journal of Islamic Education for Early Childhood, 2025)
Abstract The background of this research is based on the results of observations and interviews with the homeroom teacher, it is obtained data that in ABA 23 DENGOK Kindergarten, especially group B of 29 children, there are 4 children who do not know initial literacy properly, children are still often upside down in writing the letters b and d and upside down in write the numbers 1 2 3 4 5. Seeing this, the researcher wants to know how the initial literacy comprehension of group B children at TK Aisyiyah Bustanul Athfal 23 Dengok and wants to know what factors influence it. In the study of "group B children's writing ability", the type of research used in this study was a qualitative type. In this study, the source samples taken by researchers were purposive. The study took 4 samples of group B children at TK Aisyiyah Bustanul Athfal 23 Dengok. The type of research used by researchers is descriptive qualitative research. In this study, the techniques used in data collection were as follows: Observation, interviews, and documentation. Based on the results of research at Aisyiyah Bustanul Athfal 23 Dengok Kindergarten about children's early literacy understanding. Especially in the indicator of writing the letters of his own name, recognizing changes in sound and meaning based on changes in letters and letter positions, and mentioning numbers when shown the number symbol (saying the sound of the number symbol). Shows different results for each subject. Of the four subjects, 3 subjects experienced changes according to the indicators or researchers' expectations, but there was still one subject who was still lacking in fulfilling these indicators. Things that can affect the achievement of children's early literacy comprehension skills include: factors within the child and environmental factors that come from outside. Keywords: Early Literacy Understanding, Group B Child Literacy